The Global Paradigm Shift and the Emanation of a Network Economy - СмородинскаяНаталия Вадимовна (Journal of Economic Sociology, 2012)
The paper is devoted to emanation of a network order in the world economy under its current transition to postindustrial paradigm. This new order is described as a functional synthesis of hierarchic and market modes of social coordination, which suits both the globally modified communication environment (sharply increased dynamism, uncertainty and interdependencies) and the regime of continuous innovation. The author associates the global crisis with transformation of the world economy’s organizational code at all levels of social interactions, particularly, with the shifts from rigid vertical structures towards transformative networks, and from industries to trans-industrial clusters as a basic structural element. Special attention is paid to collaboration between three leading institutional sectors, including science, business, and government, since their model of network interactions (Triple Helix model in terms of Etzkowitz and Leydesdorff) forms an organizational matrix of knowledge-based clusters and innovation-led economies. The paper graphically illustrates clusters’ functioning as innovation ecosystems, their institutional contrasts with other types of agglomerations, and the cluster synergy effect of productivity growth, as described by M. Porter. The success of modern innovation mega clusters is exemplified by Silicon Valley (USA) and ScanBaltBioRegion (the Baltic Sea Region). In addition, the paper discusses reasons why there are no dynamic innovation clusters in the Russian economy and opportunities for their formation. The author proposes that Russia will be able to jump and change the direction and level of its development, omitting the consequential stages, if it initiates intensive collaboration with the neighboring Baltic Sea Region, learning the progressive institutional structure and adapting cluster and network technologies.